2021
DOI: 10.1021/acsapm.1c00343
|View full text |Cite
|
Sign up to set email alerts
|

Xanthan Gum Hydrogels as High-Capacity Adsorbents for Dye Removal

Abstract: Xanthan gum-based hydrogels were synthesized and investigated in an attempt to develop efficient adsorbents for removal of dye pollutants from wastewaters. The hydrogels were obtained by first esterifying Xanthan gum with maleic anhydride and subsequent cross-linking of the pendant vinyl groups via thiol-ene click chemistry with oligoethyleneglycol dithiols. The modified hydrogels were systematically characterized to assess the swelling ratio, thermal properties, point of zero charge, and chemical composition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 59 publications
1
28
0
Order By: Relevance
“…For adsorbent materials, reusability is one of the most important properties [ 22 ]. After the contaminants were absorbed by the GA-O-09/Cu 2+ xerogel, the corresponding GA-O-09/Cu 2+ xerogel was filtered from the aqueous solution, and the water was purified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For adsorbent materials, reusability is one of the most important properties [ 22 ]. After the contaminants were absorbed by the GA-O-09/Cu 2+ xerogel, the corresponding GA-O-09/Cu 2+ xerogel was filtered from the aqueous solution, and the water was purified.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, thermodynamic studies [ 22 ] were performed and are shown in Table 3 to study the influence of the temperature on the adsorption process of dye onto GA-O-09/Cu 2+ hydrogel. It could be found that the obtained values of the Gibbs free energy change ΔG 0 were negative and increased with the temperature, which indicated that the adsorption of dye molecules onto the GA-O-09/Cu 2+ hydrogel was spontaneous in nature and became less favorable with an increasing temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, environmental pollution has brought serious problems threatening human life and health, [1] in which industrial wastewater, such as print and dye, is main pollution source [2] . For example, methyl violet (MV) and rhodamine B are widely used in textile, pharmaceutical, and biological dyes [3,4] and they are recognized as a carcinogenic and mutagenic agent to living organisms [5,6] . Thus, it is necessary to remove methyl violet from wastewater by simple and high‐efficient route such as photocatalytic technology [7] .…”
Section: Figurementioning
confidence: 99%
“…[2] For example, methyl violet (MV) and rhodamine B are widely used in textile, pharmaceutical, and biological dyes [3,4] and they are recognized as a carcinogenic and mutagenic agent to living organisms. [5,6] Thus, it is necessary to remove methyl violet from wastewater by simple and high-efficient route such as photocatalytic technology. [7] To achieve this goal, high-performance photocatalysts are required to promote removal of pollutants from wastewater.…”
mentioning
confidence: 99%
“…The high number of carboxyl and hydroxyl functional groups on the surface of xanthan gum allows its functionalization with the aid of modification approaches, for example, chemical treatment of bio-composite systems. [19,20] Njuguna et al [21] grafted dithiols to xanthan gum and used it as an adsorbent for Gentian Violet. Liu et al [22] used xanthan gumgraphene oxide hybrid aerogels to remove Methyl Blue (MB) and Rhodamine B from wastewater.…”
Section: Introductionmentioning
confidence: 99%